Clinical and Patient Reported Outcomes Pre- and Postsurgical Treatment of Symptomatic Uterine Leiomyomas: A12-Month Follow-up Review of TRUST, a Surgical Randomized Clinical Trial Comparing Laparoscopic Radiofrequency Ablation (LAP-RFA) and Myomectomy. Issue 5 (May 2022) - Yu, Steve; Bhagavath, Bala; Shobeiri, S. Abbas; Eisenstein, David; Levy, Barbara
Abstract : (Abstracted from J Minim Invasive Gynecol 2022; doi: 10.1016/j.jmig.2022.01.009) Uterine leiomyomas (ULs) affect a large population of women in the United States. Despite the high incidence of women with symptomatic ULs, the number of surgical procedures performed annually is fewer than 250, 000.